Impact of Technology Innovation and R&D on Firms’ Performance in Nepal’s Service Sector - Roy, Dharmdev (Nepalese Journal of Finance, 2025)
This study examines impact of technology innovation and R&D on firms’ performance in Nepal’s service sector. Firms’ performance is the dependent variable. Similarly, the selected independent variables are technology adoption rate, innovation investment, market competition, regulatory environment and employee training in technology. The study is based on the primary data with 132 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and impact of technology innovation and R&D on firms’ performance in Nepal’s service sector on firms’ performance in Nepal’s service sector. The study indicates that technology adoption rate is positively correlated to firms’ performance. It indicates that high technology adoption rate leads to increase the firms’ performance. Similarly, innovation investment is positively correlated to firms’ performance. It indicates that higher the innovation investment leads to increase the firms’ performance. Likewise, market competition is positively correlated to firms’ performance. It indicates that market competition leads to increase the firms’ performance. Further, regulatory environment is positively correlated to firms’ performance. It indicates that higher the regulatory environment, higher would be the f irms’ performance. Moreover, employee training in technology is positively correlated to firms’ performance. It indicates that higher the employee training in technology leads to increase the firms’ performance.